Elaboración y evaluación de tres tipos de Bocashi con la aplicación de microorganismos eficaces (EM) en diferentes UPAs de la comunidad La Matara, cantón Saraguro. - Sosoranga Paqui, Claudio (2018)
With the objective of contributing to the improvement of soil fertility of “La Matara” community through the application of Bocashi made with organic residues of the UPAs, a randomized block experiment was carried out with three replications, three doses of hand-crafted EM and EM-commercial plus a witness. Through a survey it was possible to determine that the families of “La Matara” community are dedicated to the cultivation of self-consumption products and a surplus is sold in the market of Saraguro city, in the same way to the raising of animals, while the residues of harvests, as well as the manure of domestic animals, constitute an important source to generate fertilizers. With increases of the doses of EM in the fertilizer, it was possible to raise the values of 21% total nitrogen, 34% phosphorus, 132% potassium and 12% organic matter all with respect to the control, in a decomposition stage of the Bocashi that had duration of 30 days. Another aspect to emphasize is the similar behavior between the EM - Commercial and EM - Handicraft; in the C / N ratio in general, there is a difference of up to 10% between the control and the EMa and the pH of the Bocashi batteries are in the permissible ranges with values ranging from 5.4 to 7.0. The farmers of the “La Matara” community were trained in the elaboration of Bocashi with the incorporation of EM Artisanal. Keywords: Bocashi, EM-Handicraft, EM-Commercial, organic fertilizer, nutrients, effective microorganisms.